Synthesis and Characterization of Silver Nanoparticles Using Prodigiosin Pigment and Evaluation of Their Antibacterial and Anti-Inflammatory Activities - Alaa, Oulan; Hassan, Nadham (Iraqi Journal of Science, 2021)
This study focused on the biological synthesis of silver nanoparticles (AgNPs), using prodigiosin pigment produced by Serratia marcescens. The effect of parameters such as pH, temperature, time, with various concentrations of silver nitrate (AgNO3) and prodigiosin on the synthesis of AgNPs were also studied. Optimized results of the biosynthesis process revealed an increase in the intensity of Surface Plasmon Resonance (SPR) bands of nanoparticles with shifting at the wavelength of 400 nm. In addition, optimum synthesis of AgNPs was achieved at pH 12, temperature 55℃, and reaction time 24 h, with concentrations of prodigiosin, as a reducing agent, of 12.5 µg/ml and silver ion concentration of 1 mM. Measurement of the size of silver nanoparticles by SEM diffraction revealed a value of 30 nm. Finally, the minimum inhibitory concentration of AgNPs against pathogenic bacteria was 32 µg/ml for Staphylococcus aureus and Pseudomonas aeruginosa. The results of anti-inflammatory effects of Ag NPs obviously demonstrated that the infections of test animals treated with AgNPs were completely healed after 4 days of treatment, while the animals treated with fucidin (as control) did not exhibit any healing.